2017
DOI: 10.1089/aid.2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

HIV Resistance and Prevention of Mother-to-Child Transmission Regimen in HIV-Infected Infants in Northern Tanzania

Abstract: Prevention of mother-to-child transmission (PMTCT) guidelines recommend that all HIV-infected pregnant women receive antiretroviral therapy (Option B) and HIV-infected infants should initiate therapy with a protease inhibitor-based regimen; however, implementation of these guidelines has lagged in many resource-limited settings. Tanzania only recently implemented these guidelines with little country-specific data to inform whether HIV non-nucleoside reverse transcriptase inhibitor (NNRTI) resistance was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Only five of nine HIV-infected children (55.6%) in our study were referred to the CTC, and a previous study from Tanzania found that a mere one third of children with an early positive PCR test had documented referral to therapy [ 20 ]. The clinical course of HIV infection is often aggressive in children not offered ART.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Only five of nine HIV-infected children (55.6%) in our study were referred to the CTC, and a previous study from Tanzania found that a mere one third of children with an early positive PCR test had documented referral to therapy [ 20 ]. The clinical course of HIV infection is often aggressive in children not offered ART.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, HIV resistance may threaten the success of PMTCT activities. Other studies have demonstrated that resistance to non-nucleoside reverse transcriptase inhibitors such as nevirapine is common in HIV -infected infants in Tanzania [ 20 , 21 ]. Therefore, monitoring of resistance to all classes of ARVs is required both on population and individual level in order to prevent MTCT.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent archived NNRTI mutation was K103N, predominant among viraemic adolescents. By contrast, Dow et al also found the K103N mutation to be more prevalent among virally suppressed ALHIV in Tanzania, with no distinction between viraemic and non‐viraemic [41]. Nonetheless, the higher presence of this mutation could be explained by the important exposure of these adolescents to nevirapine‐based ART after exposition during delivery [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used DBS-based testing to perform population-level assessments of the frequency of drug resistance in HIV-1 [ 23 25 ] or to analyze ART outcomes in HIV-1-infected patients [ 26 28 ]. However, to our knowledge, no studies have attempted to use DBS testing to prospectively inform treatment decisions for HIV-1 or HIV-2-infected individuals in a programmatic setting.…”
Section: Discussionmentioning
confidence: 99%